Solitary fibrous tumors from A to Z: a pictorial review with radiologic-pathologic correlation - Fatmaelzahraa Abdelfattah Denewar; Mitsuru Takeuchi; Doaa Khedr; Fatma Mohamed Sherif; Farah A. Shokeir; Misugi Urano; Ahmed E. Eladl (Insights into Imaging)
Abstract Solitary fibrous tumors (SFTs) represent a rare subset of mesenchymal neoplasms, affecting 1–2 per million people, with no gender preference. They demonstrate indolent behavior, frequent asymptomatic presentation, and widespread anatomical involvement. At imaging, SFTs typically appear as well-defined, predominantly hypervascular masses with varying degrees of cystic change and necrosis, though calcification is rare. Avid heterogeneous enhancement is typical following intravenous contrast administration, with multiple blood vessels observed at the periphery. Although findings on CT and MRI alone are generally nonspecific, a frequent feature of SFTs at MRI is the presence of rounded or linear low signal intensity foci on T1- and T2-weighted images, corresponding to the fibrous and collagenous content. Nevertheless, because the imaging features of SFTs overlap with those of many benign and malignant tumors, histologic confirmation is required for the final diagnosis. A comprehensive understanding of SFTs’ multifaceted clinical, pathological, and radiological presentations across various organs is crucial for accurate diagnosis and effective management. Critical relevance statement A comprehensive understanding of the classic radiological and pathological features of solitary fibrous tumors across various organs is crucial for accurate diagnosis and effective management. Key Points Solitary fibrous tumors (SFTs) are rare hypervascular fibrous tumors with indolent behavior. Imaging features of SFTs overlap with many other tumors, necessitating histologic confirmation. Understanding SFTs’ radiological presentations is crucial for accurate diagnosis and effective management. Graphical Abstract